Turning Mothers into Freelancers: Is It Fit as Empowerment? - Arrizqi, Dhiya'; Arifianto, Chandra Fitra (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Women's empowerment has become a topic of discussion in efforts to improve the quality of women's welfare. This research explores the role of married women (or mothers) as freelancers in convection companies in South Tangerang. The main focus of this research is to provide an overview of the potential of family workers, especially women, in the context of freelance work. With a qualitative approach, researchers use interviews, observation, and documentation to obtain data. There were four informants, namely mothers who worked as freelancers. Meanwhile, the key informant in this research is the Human Resources Department, which acts as a freelancer recruiter. The questions asked adopted the Multicultural Psychological Empowerment Scale and were in the form of open questions. The analysis technique used is data triangulation. The research results show that empowering women who have families is a process that allows them to have control over their lives and destiny. The empowerment process involves increasing access to employment opportunities and financial independence. It is hoped that the results of this research will provide a comprehensive view of the benefits of women's empowerment for individuals, communities, and society.